Commercial vegetable and polyculture fish production in Bangladesh: their impacts on income, food consumption, and nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
In rural areas of Bangladesh, poverty is pervasive and associated with high rates of malnutrition especially among preschool children and women. Apart from low levels of energy intakes, it is increasingly recognized that rice-dominated diets such as those consumed by most poor in the countryside may not supply all micronutrients required for a healthy life and productive activities. Children and women are particularly vulnerable to these micronutrient deficiencies as they face relatively higher requirements for growth and reproduction.